If x + 1/x = 6, find
(i) x – 1/x
(ii) x2 – 1/x2.
Answer :
(i) We know that
(x – 1/x)2 = x2 + 1/x2 – 2
It can be written as
(x – 1/x)2 = x2 + 1/x2 + 2 – 4
(x – 1/x)2 = (x + 1/x)2 – 4
Substituting the values
(x – 1/x)2 = 62 – 4 = 32
So we get
x – 1/x = ± √32 = ± 4√2
(ii) We know that
x2 – 1/x2 = (x – 1/x) (x + 1/x)
Substituting the values
x2 – 1/x2 = (± 4√2) (6) = ± 24 √2
More Solutions:
- Prove that x2 + 1/x2 = x3 + 1/x3 = x4 + 1/x4.
- If x – 2/x = 3, find the value of x3 – 8/x3.
- If a + 2b = 5, prove that a3 + 8b3 + 30ab = 125.
- If a + 1/a = p, prove that a3 + 1/a3 = p (p2 – 3).
- If x2 + 1/x2 = 27, find the value of x – 1/x.
- Find the value of 3×3 + 5x – 3/x3 – 5/x.
- If x2 + 1/25×2 = 8 3/5, find x + 1/5x.
- If x2 + 1/4×2 = 8, find x3 + 1/8×3.
- If a2 – 3a + 1 = 0, find
- If a = 1/ (a – 5), find